Rwanda Climate Services for Agriculture: Farmers willingness to pay for improved climate services - Tesfaye, Abonesh; Hansen, James; Kagabo, Desire; Birachi, Eliud Abucheli; Radeny, Maren A.O.; Solomon, Dawit (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
This willingness-to-pay (WTP) study aims to understand how Rwandan farmers value the improved characteristics of agricultural climate services introduced to them in a choice experiment (CE) setting; estimate how Participatory Integrated Climate Services for Agriculture (PICSA) and Radio Listener Clubs (RLC) influenced perceived value; and provide insights into how the products and services can be improved. Data were collected in November 2019 from 1525 households in each intervention category (PICSA only (n=395)), RLC only (n=321), PICSA + RLC (n=182)), and a control group from sectors where the interventions were not implemented (n=627). A random parameters logit model was used to analyse the data. The estimation was conducted by disaggregating the data into the three treatment groups and the control group that was set-up by the Rwandan Climate Services for Agriculture (RCSA) project to evaluate the effectiveness of PICSA and RLCs in improving farmers’ awareness, access, use and value of climate services. For all the treatment and control groups, results suggest that Rwandan farmers value forecast accuracy; dissemination through a combination of extension agents and the PICSA process; and bundling with market price information. PICSA participation was associated with higher WTP for all of the improved characteristics of climate services introduced as a package, as indicated by the WTP values attached to the different characteristics of these services. Accuracy of information scored the highest WTP value, particularly in the PICSA treatment group. This study suggests that to improve agricultural management planning and food security of farmers through the provision of climate services, these services need to be accurate, user-tailored, and accessible. In addition, setting up a reliable market information system and bundling with climate services may help farmers make informed decisions. Results suggest that project communication interventions increased the perceived value of climate information to farmers.